2014
DOI: 10.1021/am404875s
|View full text |Cite
|
Sign up to set email alerts
|

Negative Differential Resistance Behavior and Memory Effect in Laterally Bridged ZnO Nanorods Grown by Hydrothermal Method

Abstract: A novel memory device based on laterally bridged ZnO nanorods (NRs) in the opposite direction was fabricated by the hydrothermal growth method and characterized. The electrodes were defined by a simple photolithography method. This method has lower cost, simpler process, and higher reliability than the traditional focused ion beam lithography method. For the first time, the negative differential resistance and bistable unipolar resistive switching (RS) behavior in the current-voltage curve was observed at room… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 48 publications
(64 reference statements)
0
12
0
Order By: Relevance
“…Due to the peculiar physical properties from confined dimensions, nanostructured ZnO has been extensively applied in optoelectronic and electronic devices, such as solar cells 18 19 20 21 22 , light emitting devices 23 24 , gas sensors 25 , and photodetectors 26 . Recently, nanostructured ZnO has attracted much attention as potential candidate for RS memory device as well 27 28 29 30 31 32 33 34 35 . For one-dimensional (1D) nanostructure ZnO-based RS memories, they generally have extreme properties with ultralow leakage current in HRS, large memory window, and low switching voltage 32 33 34 35 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the peculiar physical properties from confined dimensions, nanostructured ZnO has been extensively applied in optoelectronic and electronic devices, such as solar cells 18 19 20 21 22 , light emitting devices 23 24 , gas sensors 25 , and photodetectors 26 . Recently, nanostructured ZnO has attracted much attention as potential candidate for RS memory device as well 27 28 29 30 31 32 33 34 35 . For one-dimensional (1D) nanostructure ZnO-based RS memories, they generally have extreme properties with ultralow leakage current in HRS, large memory window, and low switching voltage 32 33 34 35 .…”
mentioning
confidence: 99%
“…Recently, nanostructured ZnO has attracted much attention as potential candidate for RS memory device as well 27 28 29 30 31 32 33 34 35 . For one-dimensional (1D) nanostructure ZnO-based RS memories, they generally have extreme properties with ultralow leakage current in HRS, large memory window, and low switching voltage 32 33 34 35 . So far, polymers have been applied to the active layer in the RS devices 13 14 15 , but it is rarely to use the polymers to connect the two types of semiconductors as RS devices.…”
mentioning
confidence: 99%
“…For the first time, Chuang et al observed the negative differential resistance and bistable unipolar RS behavior in the I‐V characteristic at room temperature in laterally bridged ZnO NRs synthesized by hydrothermal route. Specifically, the RS behavior and memory mechanism in vertically aligned ZnO NR‐based devices with a remarkable separated boundary at the NR/NR interface was not discussed yet.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, one‐dimensional (1D) ZnO nanomaterials (NMs) have been vastly studied because both their functional properties and highly controllable morphology make them central building blocks for understanding nanoscale phenomena and realizing nanoscale devices , . Owing to its specific optical and electrical properties due to high surface to volume ratio and quantum confinement effect, one‐dimensional ZnO nanomaterials have great potential applications in nanogenerators, photocatalysis, surface acoustic waveguides,, humidity sensors,, as well as in light‐emitting diode, sensors, solar cells,, photodetectors,, optical switches, field emission devices,, and resistive random access random memory . In addition, surface functionalization or by coupling the different properties of ZnO based semiconducting hybrids can expand the ZnO NMs applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation